Genetic heterogeneity of platelet glycoproteins Ia and IIIa and the risk of spontaneous miscarriages. (3rd June 2017) - Vlachadis, Nikolaos; Tsamadias, Vasileios; Vrachnis, Nikolaos; Kaparos, Georgios; Vitoratos, Nikolaos; Kouskouni, Evaggelia; Economou, Emmanuel
Abstract: Objective: The aim of this study was to investigate the association between the genetic heterogeneity of platelet glycoproteins Ia (GpIa-C807T) and IIIa (GpIIIa-PlA1/PlA2) and spontaneous abortions. Study design: Two hundred and twenty two women with a history of unexplained spontaneous miscarriages and no successful pregnancy, and 60 fertile women serving as controls were genotyped for the GpIa-C807T and GpIIIa-PlA1/PlA2 polymorphisms by pyrosequencing. Results: In comparison with the common alleles homozygotes, GpIa-807T and GpIIIa-PlA2 carriers had an increased risk of fetal loss (OR = 3.36, 95%CI: 1.85–6.11, p  < 0.001, and OR = 2.58, 95%CI: 1.30–5.13, p  = 0.006, respectively). For subjects who were combined carriers of the GpIa-807T and GpIIIa-PlA2 alleles, the risk increased further (OR = 9.13, 95%CI: 2.99–27.82, p  < 0.001). The above ORs were highest for women who were younger than 30 years of age. Conclusions: The GpIa-C807T and GpIIIa-PlA1/PlA2 polymorphisms and more pronouncedly their combination are associated with increased risk of spontaneous abortions. The correlations were stronger for younger patients. Our results indicate that GpIa-807T and GpIIIa-PlA2 are susceptibility alleles for fetal loss in the Greek population.